An Anonymous Persian Work – “Hikayat”: A Source on the History of the Volga-Ural Region - Gibadullin I.R. (Золотоордынское обозрение)
Research objectives: To introduce into scholarly circulation the Russian translation of a little-known Persian source on the history of the Volga-Ural region in the 14th–18th centuries and the Bashkir uprising of 1735–1740. Research materials: Currently, there is a small array of Tatar arabographic sources containing information on the history of Turkic-Tatar statehood in the Volga-Ural region, the number of which materials can be literally counted on the fingers. The work of the anonymous author, entitled “Hikayat”, and included in the composite manuscript which is stored in the Library of the Institute of Oriental manuscripts of the Russian Academy of Sciences in St. Petersburg, is almost the only known Persian work on the history of the Volga-Ural region. Therefore, it is an important source on the history of this region, especially if we consider that it was written by a local author and reflects the features of the regional Volga-Ural historical narrative tradition. This publication contains an introductory article, the main part of which is a textological analysis of this work. This source is translated into Russian and introduced into scholarly circulation for the first time ever. Results and novelty of the research: The “Hikayat” can be divided into two parts that differ according to the sources used by the author and partly according to the nature of the narrative: 1) the presentation of events of the distant past, starting from the supposed arrival of Timur in Bolghar, the history of the Kazan Khanate and its conquest which concludes with a description of realities of the “Bashkir vilayet”, and an account of the willingness of local Muslims to resist Russian intervention presented as an organic continuation of the resistance of the Kazan Muslims to the expansion of the Muscovite state. Here the anonymous author relied on some oral traditions (Akhbar) and chronicles (tavarikh), employing them as written sources along with some “old Bulgarian stories” (kissakha-yi kadim-i bulgariya); 2) an account of the events which took place during the uprising of 1735–1740 on the basis of the testimony of contemporary participants and eyewitnesses, often unnamed, but sometimes mentioned by name.